Larval density, temperature and biological aspects of Chrysomya megacephala (Diptera: Calliphoridae) - Reigada, C. [UNESP]; Godoy, W. A. C. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2006)
Analisou-se o efeito de duas densidades larvais e duas temperaturas sobre a sobrevivência, fecundidade e tamanho corpóreo de C. megacephala em condições experimentais. Nenhum efeito simultâneo da densidade e temperatura foi encontrado sobre as variáveis investigadas em C. megacephala. Entretanto, foram observados efeitos isolados significativos da densidade e da temperatura sobre a fecundidade e tamanho corpóreo. A importância desses resultados para a dinâmica populacional de C. megacephala foi discutida.

The effect of larval density on the survival, fecundity and body size at two temperatures in experimental populations of C. megacephala was studied. No effect from simultaneous influence of density and temperature on life history characteristics of C. megacephala was found. Significant effects of density and temperature on survival, fecundity and body size were observed. The importance of these results for the population dynamics of C. megacephala is discussed.
Densidade larval, temperatura e aspectos biológicos de Chrysomya megacephala (Diptera: Calliphoridae)
Keywords: Chrysomya megacephala; dependência da densidade; temperatura; sobrevivência; fecundidade; Chrysomya megacephala; density-dependence; temperature; survival; fecundity